Breeding Barley for Yellow Rust Resistance: Conventional and Molecular Pursuits - Patial, Madhu; Bishnoi, Santosh Kumar; Singh, Omvir; Pal, Dharam; Pramanick, Kallol Kumar; Sharma, Neha; Kumar, Jitender (Journal of Cereal Research, 2025)
Puccinia striiformis f. sp. hordei (Psh) causing barley stripe or yellow rust is a serious threat to barley production. The most cost-effective and long-lasting strategy for combating this disease is using genetic resistance. Stripe rust resistant genes providing both qualitative and quantitative resistances to Psh have been documented and resistance breeding has adeptly developed numerous barley varieties employing both conventional and molecular methods. The creation of high-yielding, disease-resistant cultivars necessitates the identification of resistant sources, comprehension of genetic inheritance, and subsequent hybridization and selection. A significant challenge in barley breeding remains the pyramiding of multiple disease resistance genes into high-yielding germplasm. Historically, barley breeders utilized fundamental genetic approaches, mutation breeding, and hybridization. To hasten resistance breeding advanced methodologies such as doubled haploidy and molecular techniques are also adopted.